Dry Deposition of Polycyclic Aromatic Hydrocarbons in Ambient Air - Sheu, Hwey-Lin; Lee, Wen-Jhy; Su, Chun-Ching; Chao, How-Ran; Fan, Yi-Chin (Journal of environmental engineering (New York, N.Y.), 1996)
Dry deposition and air sampling were undertaken, simultaneously, in the ambient air of an urban site and a petrochemical-industry (PCI) plant by using several dry deposition plates and PS-1 samplers from January to May 1994 in southern Taiwan. The dry deposition plate with a smooth surface was always pointed into the wind. Twenty-one polycyclic aromatic hydrocarbons (PAHs) were analyzed by a gas chromatography mass spectrometer (GC MSD). The dry deposition flux of total-PAHs in urban and PCI sites averaged 166 and 211 g m 2 s˙d, respectively. In general, the PAH dry deposition flux increased with increases in the PAH concentration in the ambient air. The PAH pattern of dry deposition flux in both urban and PCI sites were similar to the pattern measured by the filter of the PS-1 sampler and completely different from the PAH pattern in the gas phase. The higher molecular weight PAHs have higher dry deposition velocities. This is due to the fact that higher molecular weight PAHs primarily associated with the particle phase are deposited mostly by gravitational settling, while the gas phase PAHs are deposited mainly by diffusion. The dry deposition velocities due to gravitational settling are much higher than those due to diffusion. When the dry-deposition-velocity ranges of gas phase PAHs were between 0.001 and 0.010 cm s, only the lower molecular-weight PAHs-Nap and AcPy-had a significant fraction of dry deposition flux contributed by the gas phase. All the remaining higher molecular-weight PAHs had more than 94.5% of their dry deposition flux resulting from the particle phase. This is due to the fact that higher molecular weight PAHs have a greater fraction in the particle phase and the dry deposition velocities of particulates are much higher than those of the gas phase.